A comparative study on selected first and third grade community social welfare centers for the elderly in South Korea - Ryu, Pilhyu 1969 (2003)
In particular, the following are objectives of the study: 1) To determine the benefits and level of satisfaction derived from the programs and services as perceived by the elderly served by the First and Third Grade Welfare Agencies; 2) To identify problems and issues in program management and operation; 3) To generate policy and program recommendation enhancing the strategies and approaches involved in the management and operation of the elderly programs and services...
"April 2003."
Vita.
Thesis (M. Social Work)--University of the Philippines Diliman.
Keywords: Older people -- Health services -- South Korea -- Kyungnam; Old age assistance -- South Korea -- Kyungnam; Community health services for older people -- South Korea -- Kyungnam; Older people -- Social service -- South Korea -- Kyungnam